A Review of UV-Vis on Polymers; Polyaniline (PANI) and Its Nanocomposites - Assem, Humphrey Darkeh; Donkor, Michael Edem Kweku; Tamakloe, Reuben Yao; Nkum, Robert K. (European Journal of Applied Sciences, 2024)
In recent years, the utilization of Polyaniline (PANI) and its nano-composites has garnered considerable attention across diverse domains encompassing electronics, sensing technologies, and energy storage applications due to their multifaceted utility. Central to the investigation of their properties is UV-Vis spectroscopy, which has emerged as an indispensable analytical tool. This review aims to shed light on recent advancements in UV-Vis spectroscopic techniques as applied to PANI films and their corresponding nano-composites. The discourse begins by explaining the fundamental principles of UV-Vis spectroscopy and its relevance in examining the electronic transitions within PANI and its nano-composites. Subsequently, the synthetic methodologies employed for fabricating PANI films and nano-composites are expounded upon, with particular emphasis on discerning the influence of various parameters on their optical attributes. Furthermore, the implications of dopants, oxidants, and nano structural configurations on the UV-Vis spectra of PANI are meticulously examined. Additionally, this review delves into the applications of UV-Vis spectroscopy in shedding more light on the structural and optical attributes of PANI-based materials tailored for specific functions such as chemical sensing, optoelectronics, and energy storage systems. Recent advancements in the development of innovative PANI nano-composites endowed with augmented optical properties are scrutinized, highlighting their potential utility across a spectrum of technological domains. Moreover, the challenges and prospective avenues in harnessing UV-Vis spectroscopy for the characterization of PANI films and nano-composites are deliberated upon, with strategies proposed to overcome limitations including spectral superposition, sample preparation intricacies, and the interpretation of complex spectra. Furthermore, prospective directions for further research endeavours aimed at leveraging the full potential of UV-Vis spectroscopy in enhancing the comprehension and application scope of PANI-based materials are mapped out.